PENGARUH GAYA KEPEMIMPINAN SITUASIONAL, BUDAYA ORGANISASI DAN MOTIVASI PADA KINERJA KARYAWAN DI PT BANK PEMBANGUNAN DAERAH BALI CABANG BADUNG - Karma, Kadek Fajar Andika; Yasa, Gerianta Wirawan; Ratnadi, Ni Made Dwi (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
This research examined the effect of situational leadership style, organizational culture and motivation on employee performance at PT Bank Pembangunan Daerah Bali Cabang Badung. This research was 95 employess at PT Bank Pembangunan Daerah Bali Cabang Badung and entire unit underneath the status of a permanent employee. Sampling was done by saturation sampling technique that is part of the non probability sampling method in which this technique sampling an even number equal to the population . Multiple regression model was used to test the influence of independent variables on the dependent variables.The results of multiple linear regression analysis showed that situational leadership style, organizational culture and motivation positive effect on the employee's performance at PT Bank Pembangunan Daerah Bali Cabang Badung. shows that the higher the situational leadership style, organizational culture and motivation will be higher the performance of employees .
Keywords: employee performance, situational leadership style, organizational culture, motivation.